Advances and recent developments in asthma in 2020 - ÖĞÜLÜR, İSMAİL (WILEY, 2020)
In this review, we discuss recent publications on asthma and review the studies that have reported on the different aspects of the prevalence, risk factors and prevention, mechanisms, diagnosis, and treatment of asthma. Many risk and protective factors and molecular mechanisms are involved in the development of asthma. Emerging concepts and challenges in implementing the exposome paradigm and its application in allergic diseases and asthma are reviewed, including genetic and epigenetic factors, microbial dysbiosis, and environmental exposure, particularly to indoor and outdoor substances. The most relevant experimental studies further advancing the understanding of molecular and immune mechanisms with potential new targets for the development of therapeutics are discussed. A reliable diagnosis of asthma, disease endotyping, and monitoring its severity are of great importance in the management of asthma. Correct evaluation and management of asthma comorbidity/multimorbidity, including interaction with asthma phenotypes and its value for the precision medicine approach and validation of predictive biomarkers, are further detailed. Novel approaches and strategies in asthma treatment linked to mechanisms and endotypes of asthma, particularly biologicals, are critically appraised. Finally, due to the recent pandemics and its impact on patient management, we discuss the challenges, relationships, and molecular mechanisms between asthma, allergies, SARS-CoV-2, and COVID-19.
Keywords: asthma biomarkers; asthma phenotypes; biological therapeutics; comorbidities; COVID-19; ALLERGEN IMMUNOTHERAPY; CLINICAL CHARACTERISTICS; ARGINASE INHIBITORS; BLOOD EOSINOPHILS; EAACI GUIDELINES; FOOD ALLERGY; RHINITIS; MANAGEMENT; OMALIZUMAB; PATHOLOGY